2021
DOI: 10.18632/aging.203109
|View full text |Cite
|
Sign up to set email alerts
|

Immunological features beyond CD4/CD8 ratio values in older individuals

Abstract: The CD4/CD8 T-cell ratio is emerging as a relevant marker of evolution for many pathologies and therapies. We aimed to explore immunological features beyond CD4/CD8 ratio values in older subjects (>65 years old) who were classified as having lower (<1.4), intermediate (1.4-2), or higher (>2) ratio values. The lower group showed a lower thymic output (sj/β-TREC ratio) and frequency of naïve T-cells, concomitant with increased mature T-cells. In these subjects, the CD4 T-cell subset was enriched in CD95+ but dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…We found that CD3 + CD4 + CD69 + T/CD3 + CD8 + CD69 + T ratio ≤ 0.2697, CD3 + CD8 + HLA-DR + T >23.255%, and CCI >5 were significantly associated with the poor ICU discharge, and CD3 + CD4 + CD69 + T/CD3 + CD8 + CD69 + T ratio was noted as an independent prognostic factor for ICU discharge. The prognostic role of low level CD3 + CD4 + CD69 + T/CD3 + CD8 + CD69 + T ratio in G - sepsis may be similar to that of low level CD4 + T/CD8 + T ratio in sepsis in previous studies, which may reflect the imbalance of T suppression/activation of adaptive immune response during pathophysiologic process in sepsis ( 44 , 45 ). In G - sepsis (versus G + sepsis), we observed that both CD3 + CD69 + T and CD3 + CD8 + CD69 + T (%) were remarkably upregulated, while CD4 + T/CD8 + T ratio, CD3 + CD4 + CD69 + T (%) and CD3 + CD4 + T were downregulated (although the latter two indexes without significant difference).…”
Section: Discussionsupporting
confidence: 70%
“…We found that CD3 + CD4 + CD69 + T/CD3 + CD8 + CD69 + T ratio ≤ 0.2697, CD3 + CD8 + HLA-DR + T >23.255%, and CCI >5 were significantly associated with the poor ICU discharge, and CD3 + CD4 + CD69 + T/CD3 + CD8 + CD69 + T ratio was noted as an independent prognostic factor for ICU discharge. The prognostic role of low level CD3 + CD4 + CD69 + T/CD3 + CD8 + CD69 + T ratio in G - sepsis may be similar to that of low level CD4 + T/CD8 + T ratio in sepsis in previous studies, which may reflect the imbalance of T suppression/activation of adaptive immune response during pathophysiologic process in sepsis ( 44 , 45 ). In G - sepsis (versus G + sepsis), we observed that both CD3 + CD69 + T and CD3 + CD8 + CD69 + T (%) were remarkably upregulated, while CD4 + T/CD8 + T ratio, CD3 + CD4 + CD69 + T (%) and CD3 + CD4 + T were downregulated (although the latter two indexes without significant difference).…”
Section: Discussionsupporting
confidence: 70%
“…+ is a sensitive indicator of human immunodeficiency, and the decrease of this ratio indicates that the body's immune function is inhibited [20][21][22]. IgE is closely related to the pathogenesis of chronic urticaria and is the key immunoglobulin that mediates the pathogenesis of the disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…29 In our study, we have obtained the same increase of the T-CD4 + /T-CD8 + ratio, increase that is based on the statistically significant decrease of T-CD8 + subset. The presented T-CD4 + /T-CD8 + ratio is becoming an emerging cellular biomarker and potentially a useful predictor of aging, 30 typically with a reduction in the ratio associating with disease, dysfunction, or poor health outcomes. [31][32][33] The differences that we have obtained in this parameter comparing to other studies can be due to the differences in both to the genetical make-up of the populations and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%